HYALURONIC ACID LIP FILLERS: CLINICAL CASE PRESENTATION - Campos, Carine; Cruz, Mirna Liz da; Guedes , Orlando Aguirre (CIPEEX, 2025)
Lip filling with hyaluronic acid (HA) is a minimally invasive alternative for treating lip aging, offering increased volume and definition. A case study reported the experience of a 43-year-old patient who, dissatisfied with her lack of lip volume, underwent volume using Renova brand HA.